HUBUNGAN KADAR ANTI MULLERIAN HORMONE (AMH) DENGAN KEBERHASILAN STIMULASI OVARIUM PADA FERTILISASI IN VITRO METODE PROTOKOL PANJANG - , RIDHO PERMANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Patient with decline oocyte number and quality assumed has lower Anti Mullerian hormone (AMH). AMH concentration which expressed by the granulosa cells of preantral and small antral follicles indirectly determine the ovarian reserve. Therefore, AMH may be used as a marker of ovarian ageing and associated with ovarian response in in vitro fertilization (IVF). Objectives: To determine the effect of Anti Mullerian Hormone (AMH) on ovarian response in IVF long protocol method. Method: This research is a retrospective cohort study in Permata Hati Fertility Clinic, IVF program-Dr. Sardjito Hospital, Yogyakarta, Indonesia. Seventy one cycle enrolled in an IVF program conducted from January 2011 through December 2013 at the Permata Hati Fertility Clinic. Results: ROC curve were used to determine cut-off AMH. With cut-off point 2.59 ng/ml, subject divided into two groups (high AMH level: â¥2.59 ng/ml and low AMH level: <2.59 ng/ml). Total dose gonadotropin was significantly different in two groups (p=0.02). High AMH and low AMH level were significantly associated with ovarian response (RR 2,05